Interventional Pulmonology and Pulmonary Hypertension Updates on Specific Topics - Aslanidis, Theodoros (IntechOpen, 2020)
This book, published by IntechOpen, focuses on interesting aspects of pulmonary medicine. The first section of the book is dedicated to interventional pulmonology, and includes updates on bronchial thermoplasty, virtual bronchoscopy, and endobronchial ultrasound. The second section highlights special aspects of pulmonary circulation and pulmonary hypertension. Throughout the book, the authors offer us not only a "vigorous" review of the current literature but also a research path to further advancement.